Open Versus Laparoscopic Surgery for Restoration of Incisional Hernia: A Case- Control Study - Malekpour Alamdari, Nasser; Hasankhani, Hamidreza; Farsi, Yeganeh; Sabet Diveshali, Babak; Gholizadeh, Barmak (Student Research in Translational Medicine, 2024)
Background and Aim: Incisional hernia is one of the most notable surgical complications that can be repaired either laparoscopically or by open surgery. This study aims to compare the surgery- related factors and surgical outcomes between these two groups. Methods: This is a retrospective single center study, investigates the surgical outcomes of patients that have underwent either open or laparoscopic surgical repair in a tertiary hospital in Tehran, between 2019- 2020. Results: 70 patients (35 in each group) enrolled the study. 71.42 % of patients were female and the mean age of total study sample was 53.12 ± 11.66 years. There were significant lower pain score, operation time, and hospitalization length in laparoscopic cohort (p< 0.05). There was no significant difference between rates of post- operative complications including seroma, hematoma, surgical site infection, and ileus (p> 0.05). Laparoscopic surgery significantly costs more than open surgery (p< 0.05). There was no case of recurrence within the 12-months after surgery. Conclusion: In conclusion, while laparoscopic surgery costs more than open surgery, it is associated with significant decrease in pain score, operation time, and hospitalization length. There is no significant difference between post-operative complications including seroma, hematoma, and surgical site infection among two groups.